A259 TREATMENTS AND OUTCOMES IN PATIENTS WITH LUNG CANCER AND CO-MORBID CIRRHOSIS IN ONTARIO FROM 2007–2016: A POPULATION-BASED STUDY - Mishra, S (J Can Assoc Gastroenterol, 2019)
BACKGROUND: Lung cancer is the most common cause of cancer-related mortality among Canadians. Patients with lung cancer and cirrhosis have historically been excluded from clinical trials evaluating cancer treatment efficacy due to perceived perioperative risk and hepatotoxicity. Thus, outcomes in this patient population are unknown. Given the increasing burden of cirrhosis in Canada, this study aimed to describe lung cancer treatments and outcomes in patients with primary lung cancer and co-morbid cirrhosis. AIMS: Aim 1: To describe the types of treatment received (surgery, chemotherapy, and radiotherapy) in patients with lung cancer and cirrhosis stratified by cirrhosis status (compensated vs. decompensated). Aim 2: To describe cancer-specific survival (CSS) in patients with lung cancer and cirrhosis stratified by cirrhosis status (compensated vs. decompensated). METHODS: We conducted a retrospective population-based cohort study using the linked administrative databases holdings of ICES. Adult patients with a diagnosis of primary lung cancer from 2007–2016 were identified based on administrative coding from the Ontario Cancer Registry. Those with co-morbid cirrhosis were identified and sorted as compensated or decompensated by validated case definitions. Baseline demographic characteristics and the receipt of surgery, chemotherapy and radiotherapy were described. Cancer-specific survival (CSS) was evaluated using Kaplan Meier curves and compared by log-rank test. The association between cirrhosis and CCS after adjusting for confounders was evaluated using multivariate Cox proportional hazards regression. RESULTS: 42,857 patients with primary lung cancer were identified (48% female, mean age of 69 years, 47% stage IV cancer, 5-year overall survival 19%). 1,244 patients had cirrhosis with 156 being decompensated. Patients with cirrhosis were more likely young, male, of lower socioeconomic status, and higher co-morbidity than those without. Patients with cirrhosis had similar surgical rates to those without (56% vs. 56%, P=0.31) but less often had chemotherapy (34% vs. 39%, P <.001) or radiotherapy (55% vs. 58%, P<.001). Overall, the median 5-year CCS was 341 days (IQR 333–349) and was 40 days shorter in those with cirrhosis (median 311 days [IQR 263–357], P <.001). After multivariate Cox regression, patients with compensated cirrhosis had a similar risk of cancer-related mortality to those without cirrhosis (HR 1.08, 95% CI 0.99–1.16, P=0.06) but those with decompensated disease had higher mortality risk (HR 1.36, 95% CI 1.12–1.65, P<.001). CONCLUSIONS: In this study, patients with lung cancer and cirrhosis have worse CCS than those without cirrhosis but this appears to be isolated to those with decompensated disease. These results can be used in treatment decisions in patients with lung cancer and co-morbid cirrhosis. [Image: see text] FUNDING AGENCIES: Thomas M. and Louise A. Brown Research Studentship (SM) and SEAMO New Clinician Scientist Development Program (JAF)